WILL ARABIA BECOME GREEN AGAIN? A GEOLOGICAL & METEOROLOGICAL APPROACH TO CONFIRMING PROPHETIC HADITH - Hikmy, Isbram Ginanjar; Nugraha, Rangga Tri (Islam Futura, 2023)
As a Muslim, the guidance used in worship comes from the Quran and Hadiths. One of the authentic Hadiths by Muslim states that Arabia will turn green again. This research aims to explain the greening of Arabia in the past and future perspectives from a geological and meteorological point of view. The method used in this study is a review study, combining the theory of plate tectonics on the Arabian Plate and the meteorological cycles that will occur in the future using the theory of natural radiative forcing in climate change. Discoveries of mollusks and fossils that lived in water in hot deserts provide evidence of past wet conditions before it turned hot again. There have been 18 warm climate cycles and 17 climate cycles since 5.3 million years ago. The results of this research indicate that Arabia will turn green again, both from a geological and meteorological approach. The geological approach estimates that Arabia will turn green again in approximately ~25 million years, while the meteorological approach suggests at least 13,000 years in the future when the Earth reaches its opposite precession peak. The influence of meteorological cycle periods is shorter compared to the long-term effects of plate movements. The possibility of Arabia turning green in the future is indeed true, in line with the statements of the Prophet's Hadith.